Effects of Neutral Endopeptidase (Neprilysin) Inhibition on the Response to Other Vasoactive Peptides in Small Human Resistance Arteries: Studies with Thiorphan and Omapatrilat. Issue 1 (February 2014) - Dalzell, Jonathan R.; Seed, Alison; Berry, Colin; Whelan, Carol J.; Petrie, Mark C.; Padmanabhan, Neal; Clarke, Amanda; Biggerstaff, Fiona; Hillier, Christopher; McMurray, John J.V.
Summary Purpose New compounds with neprilysin or neutral endopeptidase (NEP) inhibiting activity are under clinical investigation in heart failure and hypertension. We investigated the effect of NEP inhibition on the functional vasomotor responses to a range of vasoactive peptides in human blood vessels. Methods Small human resistance arteries from patients with coronary artery disease and preserved left ventricular systolic function were studied. Thiorphan (a NEP inhibitor) was compared with captopril (an ACE inhibitor) and omapatrilat (a dual NEP‐ACE inhibitor) with regard to their effects on the response of human arteries to key vasoactive peptides. Results As expected, both captopril and omapatrilat (but not thiorphan) inhibited the vasoconstrictor effect of angiotensin I (maximal response [SEM]: 27 ± 8% vehicle, 6 ± 2% captopril, 39 ± 10% thiorphan, 8 ± 7% omapatrilat, P < 0.05). Thiorphan, captopril, and omapatrilat all enhanced the vasodilator response to bradykinin (all P < 0.01). Omapatrilat markedly augmented the vasodilator action of adrenomedullin (P < 0.05), whilst thiorphan and captopril did not. None of the three inhibitors studied affected the vasodilator action of c‐type natriuretic peptide, calcitonin gene‐related peptide, vasoactive intestinal polypeptide or substance P. Conclusions NEP inhibition with thiorphan modestly augmented the vasodilator action of bradykinin, but did not potentiate the response to adrenomedullin; dual ACE and NEP inhibition with omapatrilat, as expected, markedly augmented the response to bradykinin and also potentiated the effect of adrenomedullin. Thiorphan weakly enhanced the vasoconstrictor response to angiotensin I. Neither omapatrilat nor thiorphan had any effect on the action of a range of other vasoactive peptides including CNP.